Inclusion of a preparation based on biologically active silicon into the technology of sunflower cultivation - A. A. Mnatsakanyan; G. V. Chuvarleeva; A. S. Volkova (Новые технологии)
The article presents the material obtained as a result of the research for 2017 and 2018, which was laid on leached chernozem in the central zone of the Krasnodar Territory in FSBSI «NGC named after P.P. Lukyanenko», on the basis of the agrotechnological department. The aim of the research was to study the effect of NanoSilicon mineral fertilization with microelements on the yield and quality of sunflower seeds. It was determined that treatment with the studied preparation shortens the interphase periods of sunflower by 1–2 days, increases the height by 8–12 cm and the biomass of one plant by 97–242 grams by the flowering phase. It was also found that NanoSilicon in the studied doses increases the yield and oil collection from 1 hectare. Thus, the inclusion of NanoSilicon preparation in the sunflower cultivation technology at a dose of 15/75/75 (seed treatment – 15 g/ha + spraying on seedlings – 75 g/ha + 75 g/ha in the phase of 5–7 pairs of leaves) significantly increases yield by 0,58 t/ha and oil collection from one hectare by 0,32 t/ha. As a result, 3,23 t/ha of seeds and 1,64 t/ha of oil were obtained.